Representatives of neighbouring countries and their national character as reflected in the world outlook of the Lithuanian - Papaurėlytė-Klovienė, Silvija (Lietuvių kalba, 2010)
The paper sets out to discuss character features attributed to Byelorussians, Latvians, Poles, Russians, Germans, i.e. representatives of neighbouring nations or those most prominent in the history of Lithuania as identified in the world outlook of the Lithuanian language. In other words, the paper aims at identifying ethnical stereotypes entrenched in the world outlook of the Lithuanian language. The data includes all collocations with all the words baltarusiškas (-a), latviškas (-a), lenkiškas (-a), rusiškas (-a), vokiškas (-a) in all their forms collected from the Corpus of Contemporary Lithuanian compiled at the Centre of Computer Linguistics of Vytautas Magnus University in Kaunas. The results of the analysis into actual usage have been supplemented by the results of the content analysis of international anecdotes. The methodology of research is based on conceptual analysis.The results of investigation have shown that the closest neighbours are unlikely to be the best known. Representatives of Latvia and Belarus, or countries bordering on Lithuania, have been only fragmentary reflected in the world outlook of the Lithuanian language. Poles, Russians or Germans, the latter are usually not treated as neighbours, are much better known. The language world outlook has identified Polish patriotism and sometimes self-esteem going to the extremes. Russians are thought of as open, ingenuous people whose patriotic feelings might overstep certain boundaries and pose danger. The dominant feature of German national character is their inclination to order, sometimes also rather extreme.Such features might be due to several causes. Russians and Poles make up a large part of the population of national minorities of Lithuania, which is why they are seen as slightly closer. On the other hand, Lithuania is historically related to Poland, Russia and Germany.The language world outlook tends to provide more details on negative features. The tendency also applies when discussing the national character of representatives of other nations. Most outstanding features are verbalised hyperbolically and ironically.
Keywords: none